Comparison of the Sensitivity of the Selective Membrane Extraction Method with Heating Lysis on the Detection of HPV DNA Genotyping - Nurjanah, Isnaeni; Widowati, Retno; Fajri, Hidayatul (Nursing and Health Sciences Journal (NHSJ), 2024)
Cervical cancer occupies the third position in the cause of death from all cancers in Indonesia. PCR amplification examination can be used to detect HPV DNA Genotyping. Before carrying out PCR, DNA extraction is an essential step because it can determine the sensitivity of the examination. Sensitivity of HPV DNA detection Genotyping determined by concentration, purity and dot blot hybridization. The aim of this study was to compare the sensitivity of the selective membrane extraction method with heating lysis for the detection of HPV DNA Genotyping. In this research, a qualitative descriptive research method was used using a sample swab Cervical results previously known were six positive low risk, six positive high risk and six combinations of both at Laboratory X in Jakarta. The sampling technique used is disproportionate stratified random sampling. Work is done in duplicate. From the results of test analysis Chi-Square based on concentration, the value obtained is p=0.5 (>0.05), based on purity, the value obtained is p=0.5 (>0.05) and based on the results of HPV DNA hybridization Genotyping The p value obtained was 0.5 (>0.05), meaning there was no significant difference in sensitivity between the selective membrane extraction method and the heating lysis extraction method for the detection of HPV DNA. Genotyping. In this study both extraction methods can be amplified and used in the detection of HPV DNA Genotyping. Heating lysis extraction can be the main choice for use in HPV DNA detection Genotyping because it is more time and cost efficient.